94 A CASE OF FULMINANT HEPATIC FAILURE TREATED WITH N-ACETYLCYSTEINE. (1st March 2007) - Venkatesan, J.; Soni, M.; Schwartz, T.; Bernstein, M.
Abstract : Background: Fulminant hepatic failure is one of the most challenging gastrointestinal emergencies and encompasses a pattern of clinical symptoms and pathophysiologic responses associated with rapid arrest of normal hepatic function. Hyperacute hepatic failure usually presents with liver function abnormalities, coagulopathy, encephalopathy, and multisystem failure. This is a case report of hyperacute liver failure that presented with coagulopathy and an isolated elevation of aspartate aminotransferase and normal alanine aminotransferase. The etiology for liver failure is multifactorial. In our patient, the above presentation was attributed to therapeutic misadventure: acute acetaminophen toxicity in chronic alcoholics at a very low dose. The patient had improvement of symptoms and liver function after treatment with N -acetylcysteine. Case Report: A 51-year-old male with a past medical history of hypertension on ACE-I on and off was admitted with abdominal pain, nausea, and vomiting for 4 days. The patient took six 500 mg tablets of acetaminophen over 3 days' duration. In addition, he took enalapril 40 mg for his ill health. The patient gave a history of chronic alcohol abuse. Positive physical findings on admission include hypotension, which subsequently improved, conjunctival icterus, and tenderness over the right hypochondrium. Laboratory data showed creatinine 1.9, total bilirubin 5.7, direct bilirubin 2.7, AST 11, 736, ALT 20, PT/INR 26.0/4.6, and alkaline phosphatase 141. Liver profile was repeated to check for error. Electrocardiogram showed normal sinus rhythm with left axis deviation. Abdominal sonogram showed distended gallbladder with moderate sludge, pericholecystic fluid. Acetaminophen level was 8.8. Differential diagnosis on admission included acetaminophen toxicity, shock liver, enalapril-related liver toxicity, alcoholic hepatitis, infectious hepatitis, autoimmune hepatitis, Wilson disease, and acute cholecystitis. The patient was started on intravenous N -acetylcysteine and vitamin K and was managed in intensive care with a plan for possible liver transplant. ANA; hepatitis A, B, C, D, and E; α1 -antitrypsin; ceruloplasmin; antimitochondrial Ab; and anti-smooth muscle Ab were negative. During the hospital course, the patient showed recovery in both symptoms and liver function tests. Isolated AST elevation noted for 24 hours and later ALT showed an increase followed by recovery of both AST and ALT. INR also improved. Discussion: A high index of suspicion of acetaminophen toxicity, even in low doses, is needed in patients with chronic alcohol abuse. The role of N -acetylcysteine is crucial in such patients and may be beneficial if the etiology of acute hepatic failure is unclear while investigations are being done. Isolated AST elevation was also an uncommon presentation in this patient.